Phonological Changes in Classical Arabic to Modern Arabic: A Historical Review - Iis Susiawati; Mustaien Billah; Rizka AlFajr; Dadan Mardani; Muhammad Faiz Alhaq (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
The phonology of the Arabic language, both classical and modern, is recognized for its richness and deep complexity, influenced by religious texts and traditional linguistic schools. However, research on the phonological changes from Classical Arabic to Modern Arabic remains limited and has not been extensively explored. This study aims to examine the main phonological changes that have occurred from Classical Arabic to Modern Arabic, focusing on shifts in the pronunciation of consonants and vowels as well as the social, political, and cultural factors influencing these changes. The research method employed is a literature review with a historical approach, encompassing the analysis of literature from various historical, linguistic, and classical and modern texts. The findings reveal that the major phonological changes include shifts in the pronunciation of several consonants and vowels. Additionally, it was found that social factors such as urbanization and contact with foreign languages, as well as political and cultural factors such as the spread of Islam and administrative changes, have influenced the evolution of Arabic phonology. These results provide a deeper understanding of the evolution of the Arabic language and the factors influencing it.